Soviet Planning and Spatial Efficiency The Prewar Cement Industry - Abouchar, Alan (Indiana University Press, 1971)
The cement industry provides an especially suitable framework within which to analyze the spatial efficiency of Soviet planning because of its size and rate of growth, which are among the highest in the economy; its relatively simple cost structure and limited scale economies; the widespread distribution of its raw materials, resulting in narrow and predictable regional production cost variation; and the homogeneity of use of its output, as an input into construction, which makes its demand easier to anticipate than is the demand for many other industrial materials, simplifying the problem of location and facilitating retrospective analysis.